Efektifitas Olahraga Jalan Kaki Terhadap Penurunan Depresi Pada Lansia Di Panti Werdha Mojopahit Mojokerto - Endang Susilowati (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2012)
The existence of an increasing elderly generate polemics. This is caused by the emergence of various physical problems, psychological, and social consequence of degenerative processes experienced by the elderly. The condition often led to problems of mental disorders in the elderly such as depression, cognitive disorders, phobias. In order to reduce one of the alternatives penangananya depression with exercise walking. The purpose of this study to determine the effectiveness of exercise walking to the reduction of depression in elderly in nursing Panti Mojopahit Mojokerto.The method used is the pre experimental static group comparison approach. This study aims to determine the effect of an action in the group of subjects who received treatment, then compared with a group of subjects who did not receive treatment. Data were collected using a questionnaire GDS (geriatric depression scale). The results showed that post-observation on the results obtained in experimental groups of eight elderly (80%) likelihood of depression and two elderly (20%) depression. For the control group found that the result of nine elderly (90%), depression and an elderly (10%) likelihood of depression. Result analysis of two independent samples test Mean Withney test p value = 0.000, while at the table with the level of significance Î± = 0.05, the data may be known p <Î± so that Ho refused and Ha accepted. This ni mean that sports has to walk to the decrease of the effectiveness of depression in elderly in nursing Panti Mojopahit Mojokerto. Based on the above research can be concluded that exercise has to walk to the decrease of the effectiveness of depression in elderly in nursing Panti Mojopahit Mojokerto. Expected to officers in the nursing Panti Mojopahit Mojokerto maintaining a walking exercise activities as an alternative therapy to treat depression.